PENDEKATAN UMUM DALAM SUPERVISI PENDIDIKAN - Nurul Zikrina; Mira Dwi Santika; Subandi Subandi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
This study aims to explore an effective educational supervision approach in the context of education in Indonesia, taking into account the influence of religious and cultural values. The background of this study is based on the importance of the role of supervisors in supporting teachers to achieve the educational goals that have been set. The method used is a descriptive qualitative approach, where data is collected through observation and interviews with educators as key informants. The findings of the study indicate that a collaborative and non-directive supervision approach is more effective in improving the quality of teaching, compared to a directive approach. In addition, social interaction between supervisors and teachers has been shown to be important in building better understanding and practice. The implications of this study emphasize the need for training for supervisors to develop skills in providing constructive feedback and creating a supportive working atmosphere. Thus, this study contributes to the development of better educational supervision practices, which can improve the quality of education in schools.